Effects of persuasion knowledge and other factors on advertising avoidance on Instagram: the case of the UK - Liu, Jing (2019)
Social media marketing provides huge opportunities for companies. In particular, the advent of mobile devices has enabled businesses to communicate directly with consumers through Internet marketing campaigns, regardless of location or time. However, the field of social media marketing still needs further research. Nowadays, advertising marketing can be seen everywhere, and social media is becoming more and more popular. Additionally, consumers' network experiences are accumulating, and they gradually understand the selling purpose of the advertisement, so they even intentionally avoid those marketing messages. Consequently, the purpose of this paper is to investigate the effects of persuasion knowledge and other factors on consumer responses towards Instagram advertising. There are three main research questions in this study. First one is to examine the effects of persuasion knowledge on perceived ad value and consumer avoidance reactions towards Instagram advertising, and the second question is to test the influence of perceived advertising value on advertising avoidance. The last question is to evaluate the regulating effects of brand familiarity on consumer responses. The study was designed based on the persuasion knowledge model and took Instagram as an example. Quantitative research was conducted through means of an online questionnaire to gather data within the UK. The study found that consumers with high cognitive persuasion knowledge are more likely to be sceptical of Instagram sponsored ads, and at the same time, consumers with high persuasion knowledge perceived less advertising value. Moreover, in the case of Instagram, both high persuasion knowledge and perceived less advertising value can cause advertising avoidance, including affective avoidance, cognitive avoidance and behavioural avoidance. Specifically, consumer scepticism has the most significant effects on cognitive avoidance, while the perceived value of advertising has the most significant negative effects on behavioural avoidance among all three kinds of advertising avoidance. Finally, brand familiarity was approved that can reduce avoidance behaviour.